Prevalemce and correlatesof occupational stress and the effectiveness of an intervention to manage occupational stressamong selected categoriesof employees in domestic commercial banks in the district of Colombo - Suraweera, S.A.J.K (My University, 2009)
Component one of the study validated three selected scales of instrument, the Job Content Questionnaire before its application in the main study to assess the prevalence of iso strain and the main study to assess the prevalence of iso-strain and high job strain, which measure occupational stress. opponent two was a cross-sectional study done to assess the prevalence and correlates of occupational stress in middle level managers and operational staff members in domestic commercial banks in the Colombo district. Component three was a cluster randomized controlled study carried out to assess the effectiveness of an occupational stress management intervention for middle level managers. The validated decision latitude, psychological[ demands and social support at work scales of the JCQ consisting of 22 items were found to be a valid and reliable instrument to assess occupational stress in banking worker. The problem of iso-strain I and high job strain indicating high level of occupational stress among middle level managers and operational staff members in the banks should be made aware of this problem. The health authorities too should consider this issue as a priority in occupational health and activities should be planned to manage this problem effectively.